Validation and application of a chromatographic method for evaluation of commercial vegetable oils possibly adulterated - Araújo, Katarynna Santos; Barbosa, Mariana Oliveira; Malafaia, Carolina Barbosa; Napoleão, Daniella Carla (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2018)
A method of separation, identification and quantification of fatty acid methyl esters (FAMEs) was developed by gas chromatography with flame ionization detector (GC-FID) using a basic transesterification. In this sense, there were analyzed FAMEs in commercial samples of vegetable oils from soybean and olive oil. The referred method was linear (r>0.99), accurate and precise for palmitic (C16:0), linoleic (C18:2), oleic (C18:2), linolenic (C18:3) and stearic (C18:0) acids. The limits of detection (LOD) and quantification (LOQ) were from 0.03 to 0.31 and 0.08 to 0.94 mg.mL-1 for the five fatty acids, respectively. The results demonstrated that the unsaturated fatty acids were the most abundant for the two samples, being the oleic acid (C18:1) the major in three brands of olive oil (D, E and F), and the linoleic acid (C18:2) the most abundant in soybean oil and the other brands of olive oil (G, H and I), suggesting a possible adulteration in these brands. The proposed method could be considered a tool for the investigation of adulteration in commercial vegetable oils for guaranteed reliability in the results to be comparable with correlated legislations.